Risk Factors in Derivatives Markets - Raimonda Martinkutė-Kaulienė (Entrepreneurial Business and Economics Review)
The objective of the article is to analyse and present the classification of risks actual to derivative securities. The analysis is based on classical and modern literature findings and analysis of newest statistical data.Â The analysis led to the conclusion, that the main risks typical for derivatives contracts and their traders are market risk, liquidity risk, credit and counterparty risk, legal risk and transactions risk. Pricing risk and systemic risk is also quite important. The analysis showed that market risk is the most important kind of risk that in many situations influences the level of remaining risks.